INVENTARISASI TUMBUHAN SEBAGAI PENYEDAP RASA ALAMI DI KAWASAN HUTAN DESA ENSAID PANJANG KABUPATEN SINTANG - Sri Sumarni; Charles Krispin (Universitas Quality, 2022)
AbstractThe use of plants as natural flavorings for generations has been used by the community in Ensaid Panjang Village. Natural flavoring is more in demand by the community because it is safe for consumption, then easy to process and certainly comes from the forest area around the village. The purpose of this study was to provide information on the diversity of natural flavoring plant species found in the forest area of Ensaid Panjang Village, Sintang Regency. The research method used was a survey method to determine the research location, with data collection through exploration and for interviews using the snow ball method. The analysis was carried out through identification of morphological characteristics of plants, and citation analysis and percentage use of plant parts. The results of the study found 12 species and 10 families, the highest citation value of 100% there were 7 species and the lowest citation value of 42% was type The percentage of use of plant parts was leaves (59%), fruit (25%), flowers (8%) and root crops (8%).The conclusion is that efforts to conserve natural flavoring plant habitats and forest area ecosystems in Ensaid Panjang Village must be handled appropriately by the manager, considering the use of natural flavoring plants is one of local wisdom that is not only socio-cultural but also a form of efforts made by local communities in conserving natural resources. Keywords :Natural Flavor Plants, Forest Area, Long Ensaid Village.